2006
DOI: 10.1111/j.1365-2672.2006.02930.x
|View full text |Cite
|
Sign up to set email alerts
|

Mycelium cultivation, chemical composition and antitumour activity of a Tolypocladium sp. fungus isolated from wild Cordyceps sinensis

Abstract: Aims:  To examine and illustrate the morphological characteristics and growth kinetics of Cs‐HK1, a Tolypocladium fungus, isolated from wild Cordyceps sinensis in solid and liquid cultures, and the major chemical constituents and antitumour effects of Cs‐HK1 mycelium. Methods and Results:  The Cs‐HK1 fungus was isolated from the fruiting body of a wild C. sinensis and identified as a Tolypocladium sp. fungus. It grew rapidly at 22–25°C on a liquid medium containing glucose, yeast extract, peptone and major ino… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
61
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(69 citation statements)
references
References 19 publications
0
61
0
Order By: Relevance
“…and P. hepiali [17,21,24,25], Tolypocladium sp. and T. sinensis [2,21,23,26], and Pseudogymnoascus roseus [27]. Clustering analyses have indicated diversified phylogenetic patterns when different C. sinensis reference sequences were used for the analyses [2,3,19,22,23,[28][29][30].…”
Section: Introductionmentioning
confidence: 99%
“…and P. hepiali [17,21,24,25], Tolypocladium sp. and T. sinensis [2,21,23,26], and Pseudogymnoascus roseus [27]. Clustering analyses have indicated diversified phylogenetic patterns when different C. sinensis reference sequences were used for the analyses [2,3,19,22,23,[28][29][30].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies on the morphology, growth kinetics, and main chemical components of solid or liquid cultures of Tolypocladium fungi isolated from wild Cordyceps sinensis, showed that the in vitro hyphae mycelium of Tolypocladium presented much higher contents of adenosine (1116.8 µg vs. 264.6 µg) than when the fungus was directly isolated from C. sinensis [18]. Similarly to what was observed for Tolypocladium, adenosine could represent a potential biomarker of the hyphae growth morphology state as observed in our strain.…”
Section: Dothiora Sp Biomarkers Related To Growth Morphologymentioning
confidence: 99%
“…The mycelial protein content of P. hepiali (36.7%) obtained in this study is more than the mycelial protein contents reported by Ulziijard and Mau [14] for Sparassis crispa (32.61%), Inonotus obliquus (25.59%), Grifola frondosa (26.40%) and Anthrodia camphorata (9.49%). Leung et al [15] found slightly higher protein content in mycelium of a Tolypocladium sp. ).…”
Section: Comparison Of Chemical Componentsmentioning
confidence: 95%